2017
DOI: 10.1186/s12888-017-1570-1
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial to improve health and reduce substance use in established psychosis (IMPaCT): cost-effectiveness of integrated psychosocial health promotion

Abstract: BackgroundThere is mounting evidence that people with severe mental illness have unhealthy lifestyles, high rates of cardiovascular and metabolic diseases, and greater risk of early mortality. This study aimed to assess the cost-effectiveness of a health promotion intervention seeking to improve physical health and reduce substance use in people with psychosis.MethodsParticipants with a psychotic disorder, aged 18-65 years old and registered on an enhanced care approach programme or equivalent were recruited f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…For secondary outcomes also no significant differences were found at 12-month follow-up. At 24 months follow-up, however, results were similar (10-year risk of CVD was 8.7% (SD 6.0%) in the CHANGE group vs. 7.7% (SD 5.7%) in the care coordination group, and 8.0% (SD 6.3%) in the treatment as usual group ( p = 0.24) [ 26 , 43 ]).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…For secondary outcomes also no significant differences were found at 12-month follow-up. At 24 months follow-up, however, results were similar (10-year risk of CVD was 8.7% (SD 6.0%) in the CHANGE group vs. 7.7% (SD 5.7%) in the care coordination group, and 8.0% (SD 6.3%) in the treatment as usual group ( p = 0.24) [ 26 , 43 ]).…”
Section: Resultsmentioning
confidence: 90%
“…At 12-month and 15-month follow-up, no significant results were revealed in Quality of Life for both the mental and physical components. Of the secondary outcomes there was only a significant improvement in HDL cholesterol [ 32 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…IMPaCT randomised controlled trial). Thi s section provides a summary of work published in Gaughran et al 175,176 and Heslin et al 177 Parts of this text have been reproduced from Gaughran et al 176 This is an Open Access article distributed in accordance with the terms of the Creative Commons Attribution (CC BY 4.0) license, which permits others to distribute, remix, adapt and build upon this work, for commercial use, provided the original work is properly cited. See: http://creativecommons.org/licenses/by/4.0/.…”
Section: Discussionmentioning
confidence: 99%
“…To address the key question of value for money in a resource-constrained health-care system, we conducted a comprehensive within-trial economic evaluation of the IMPaCT HPI to inform future decisions about its adoption into the NHS. This section summarises the work published in Heslin et al, 177 with further unpublished data presented in Appendix 4.…”
Section: Work Package 3: Economic Evaluation Section Introductionmentioning
confidence: 99%
“…Currently, there is a lack of cost effectiveness research examining supervised exercise programs in SMI, apart from two large scale unsuccessful intervention trials which reported no evidence for their cost effectiveness (28,96). No EIP studies to date have reported on cost effectiveness.…”
Section: Program Costs and Cost Effectivenessmentioning
confidence: 99%